2020
DOI: 10.1086/710240
|View full text |Cite
|
Sign up to set email alerts
|

Climate Risk and Beliefs in New York Floodplains

Abstract: Any opinions expressed in this paper are those of the author(s) and not those of IZA. Research published in this series may include views on policy, but IZA takes no institutional policy positions. The IZA research network is committed to the IZA Guiding Principles of Research Integrity. The IZA Institute of Labor Economics is an independent economic research institute that conducts research in labor economics and offers evidence-based policy advice on labor market issues. Supported by the Deutsche Post Founda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 71 publications
(68 reference statements)
1
38
0
4
Order By: Relevance
“…In analysis 2, the values of properties that had not flooded previously but were designated as flood-risk zones declined. This finding is consistent with that of Gibson et al (2019). The values of the properties that were inundated by previous floods and were located in the designated flood risk zones continuously declined, whereas the values of properties that were inundated by previous floods but were not located in the designated flood zones displayed a slower decline after the disclosure of flood risk information, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In analysis 2, the values of properties that had not flooded previously but were designated as flood-risk zones declined. This finding is consistent with that of Gibson et al (2019). The values of the properties that were inundated by previous floods and were located in the designated flood risk zones continuously declined, whereas the values of properties that were inundated by previous floods but were not located in the designated flood zones displayed a slower decline after the disclosure of flood risk information, although the difference was not statistically significant.…”
Section: Discussionsupporting
confidence: 88%
“…Indaco et al (2019) reported that the prices of properties whose flood risk was downgraded in the updated FEMA flood risk maps increased. Gibson et al (2019) showed that properties that did not flood during Hurricane Sandy in 2012 but included in the new floodplain maps suffered price drops after the release of the new maps. These studies have confirmed that the disclosure of new flood risk information affects real estate property values.…”
Section: Introductionmentioning
confidence: 99%
“…Of the few non-cross-sectional studies, results are mixed: In Center County, PA, rezoning into a floodplain reduced property values, but rezoning out of a floodplain had no effect (9). In New York City, NY, the release of preliminary new flood maps reduced property values, but the effect differed sharply between properties that had and had not flooded during Superstorm Sandy (10).…”
mentioning
confidence: 99%
“…See alsoGibson et al (2019), who study the effect of the 2012 B-W reforms, flood map changes, and the impact of Hurricane Sandy on property values in New York.…”
mentioning
confidence: 99%